2007
DOI: 10.1080/00952990701315459
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Among Suburban Drug Court Participants

Abstract: The issue of co-occurring disorders is of concern to the Criminal Justice field, including drug courts. To assess the potential co-occurrence of substance use- and mental health-related diagnoses, the Psychiatric Diagnostic Screening Questionnaire and similar instruments was administered to suburban drug court clients. Based on the screening, one quarter to one half of the 108 participants would be referred for follow-up for a mental health issue; women would be referred at a greater rate than men. There is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Two studies used validated screening measures for anxiety and depression symptoms (Beck Anxiety Inventory and Beck Depression Inventory-II). Rates of moderate-severe or severe anxiety were 12%35 and 35%34. Rates of depression warranting referral were 20.4%35 and 42% 34.…”
Section: Epidemiological Data On Drug Court Participantsmentioning
confidence: 98%
See 2 more Smart Citations
“…Two studies used validated screening measures for anxiety and depression symptoms (Beck Anxiety Inventory and Beck Depression Inventory-II). Rates of moderate-severe or severe anxiety were 12%35 and 35%34. Rates of depression warranting referral were 20.4%35 and 42% 34.…”
Section: Epidemiological Data On Drug Court Participantsmentioning
confidence: 98%
“…Structured Clinical Interview for DSM Disorders). Where drug court participants were recruited and mental health measures subsequently administered,3335 between 25 and 42 percent of participants were identified as having a psychiatric illness. Two studies used validated screening measures for anxiety and depression symptoms (Beck Anxiety Inventory and Beck Depression Inventory-II).…”
Section: Epidemiological Data On Drug Court Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a demographic perspective, a large portion of the sample was receiving government assistance, was unemployed, and had less than a high school education. Additionally, as might be expected, there was a different gender composition than what is found in standard drug court (21). In standard drug courts, the majority of participants are male, whereas within the FTC population, the majority of participants are female.…”
Section: Discussionmentioning
confidence: 76%
“…Scant research has examined the explicit impact of trauma history on drug court treatment outcomes; however, a body of evidence demonstrates a clear link between alcohol/drug abuse treatment attrition and histories of physical and sexual abuse (e.g., Amaro, Nieves, Johannes, & Cabeza, 1999; Claus & Kindleberger, 2002; Kang, Deren, & Goldstein, 2002). In a study on mental health issues among drug court participants, Weitzel, Nochajski, Coffey, and Farrell (2007) found that 32 of 108 participants reported traumatic events in their past, and 25% of these participants met the criteria for post-traumatic stress disorder (PTSD). Hagedorn and Willenbring (2003) similarly found that PTSD was one of the most common diagnoses among drug court participants in their study.…”
Section: Treatment Attrition and Trauma-related Symptomsmentioning
confidence: 99%